TO THE ISSUE OF INTERNATIONAL REGULATION OF COMBINATING ACTS OF INLAWFUL INTERFERENCE WITH THE CIVIL AVIATION AREA - Чуб, Г. М. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2008)
The article deals with the issues of combating acts of unlawful seizure and hijacking of aircraft, which are governed by the norms of the Tokyo, the Hague and Montreal conventions and national legislation.